KEMAMPUAN POLISI LALU LINTAS DALAM MEMBERIKAN BANTUAN HIDUP DASAR PADA KORBAN KECELAKAAN - Abiddin, Andi Hayyun; Arif Mulyadi, Arif; Putri Setyorini, Putri (Jurnal Keperawatan Malang, 2024)
Background: The increase in the number of motorized vehicles in Nganjuk Regency is related to the increase in traffic accidents. Traffic police play a very important role in reducing or preventing the impact of traffic accidents, especially cardiac arrest. Police who are trained in providing basic life support can reduce the risk of death for accident victims with cardiac arrest. Objective: To identify the ability of basic life support for accident victims provided by traffic police in the Nganjuk Police work area. Method: Descriptive quantitative observational with a population of 85 Nganjuk Regency traffic police. A total of 30 respondents were taken through purposive sampling technique. Observation sheets based on the American Health Association (AHA) version 2020 were used to collect data. Descriptive data analysis by displaying frequency distribution and percentages was used in this study. The study period was in February 2024. Results: Respondents with a good category were 19 (63.3%), respondents with a sufficient category were 6 (20.0%), and the poor category were 5 (16.7%). Implications: The majority of respondents described their ability to provide basic life support in the range of sufficient to good. This shows that the basic life support capabilities for accident victims provided by traffic police in the Nganjuk Police work area are included in the good category.